Evaluasi efektivitas konseling terhadap tingkat kecemasan klien resiko tinggi HIV/AIDS - Putu Artawan Prayoga; Lalu Sulaiman (Riset Informasi Kesehatan, 2020)
Background: HIV / AIDS has become a global public health problem like Indonesia, with a fairly large percentage of 80% by 2020. The increase in cases is due to the absence of symptoms or special characteristics that mark the physical characteristics of ODHA and the absence of typical health complaints related to HIV. / AIDS. Anxiety is one of the things that will arise for clients in the form of feelings of fear and caution and unclear and unpleasant vigilance. The emergence of discrimination and classification will affect the quality of life and the level of welfare. Therefore, this study is important to determine the level of effectiveness of counseling interventions on clients' anxiety level with HIV / AIDS. The purpose of this study was to evaluate the effectiveness of the counseling intervention on the anxiety level of high-risk clients with HIV / AIDS. Method: Pre-experimental method with a one-group pre-test approach was developed in this study. HARS is an instrument and purposive sampling for data processing with a sample size of 21 people. Results: The results showed that the respondents had different characteristics, 70% male respondents, 30% of respondents aged 25-30 years, 50% had a high school education, and most worked as hotel employees. Conclusion: Counseling interventions can reduce clients' anxiety levels with a high risk of HIV / AIDS from 100% to 62%; in other words, counseling interventions affect clients' anxiety levels with a high risk of HIV / AIDS.